STUDY OF THE INFLUENCE OF INTERNAL STRESSES ON THE MICROSTRUCTURE OF COATINGS DURING ELECTROLYTIC RUBBING - Gimaltdinov, I.; Sadykov, M.; Adigamov, N.; Kalimullin, M.; Voinash, S.; Vornacheva, I.; Malikov, V. (Eurasian Physical Technical Journal, 2026)
The paper studies the effect of residual stresses on the microstructure and mechanical properties of metal coatings formed by electrolytic rubbing. The dependence of the internal stress level on the current density, anode rotation speed, electrolyte composition and deposited layer thickness is established. It is shown that with an increase in current density from 50 to 100 A/dm² and a deposition rate of up to 16.6 μm/min, residual stresses vary within 23–34 kg/mm². The addition of ascorbic acid, nickel and manganese chlorides promotes an increase in stresses by 5–10% and simultaneously increases the microhardness of the coatings. A decrease in residual stresses is noted upon reaching a layer thickness of 0.03–0.04 mm, followed by stabilization at a level of 10–12 kg/mm². The results of the work can be used to optimize technological modes of restoration and hardening of agricultural machinery parts, ensuring increased accuracy and quality of metal coatings.